2014
DOI: 10.3168/jds.2014-8297
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Relationship between the efficiency of utilization of feed nitrogen and 15N enrichment in casein from lactating dairy cows

Abstract: The objective of the present study was to evaluate the relationship between the efficiency of conversion of feed N into milk N [N-use efficiency (NUE)] and (15)N enrichment of milk casein from lactating cows fed corn silage-based diets. Samples of feeds and milk were obtained from 3 experiments with lactating dairy cows. All diets were based on corn silage and were designed to evaluate the effects of (1) diets with different ratios of effective rumen-degradable protein to fermentable metabolizable energy (expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
0
6
1
Order By: Relevance
“…NUE ranged between 0.11 and 0.15 g/g) and did not respond to dietary treatment in this study (Table 3). Second, previous study suggested microbial protein synthesis contributes to N isotopic fractionation (Cabrita et al, 2014). However, there was little effect of dietary treatments on microbial protein synthesis, as indicated by both PD and MCP/FME calculations in this study.…”
Section: Dietary Wsc and Nitrogen Isotopic Fractionationcontrasting
confidence: 60%
“…NUE ranged between 0.11 and 0.15 g/g) and did not respond to dietary treatment in this study (Table 3). Second, previous study suggested microbial protein synthesis contributes to N isotopic fractionation (Cabrita et al, 2014). However, there was little effect of dietary treatments on microbial protein synthesis, as indicated by both PD and MCP/FME calculations in this study.…”
Section: Dietary Wsc and Nitrogen Isotopic Fractionationcontrasting
confidence: 60%
“…The weaker correlation (r 2 = 0.29) between Δ 15 N and MNE found by Cabrita et al (2014) in dairy cows fed diets differing mainly in the amount and quality of rumen degradable protein compared with that (r 2 = 0.83) found by Cheng et al (2013) was ascribed to a high contribution of rumen N efficiency, in contrast to liver metabolism, to MNE. That is, a strong relationship between MNE and this isotopic marker would be evident provided that metabolism contributes to a high proportion of this overall N efficiency.…”
Section: Discussionmentioning
confidence: 69%
“…However, to date, the potential contribution of rumen digestion to natural 15 N bioaccumulation and thus its impact on the relationship between ENU and the animal isotopic N fractionation (i.e. Δ 15 N animal-diet ) has been discussed (Cabrita et al, 2014;Cantalapiedra-Hijar et al, 2015) but not properly assessed. The aim of this study was to evaluate to what extent the relationship between Δ 15 N animal-diet and ENU was impacted by digestive processes, in contrast to metabolism, in dairy cows fed diets similar to those previously tested (Cantalapiedra-Hijar et al, 2015), and in which duodenal flow of N fractions were measured.…”
Section: Introductionmentioning
confidence: 99%
“…Different studies have analyzed the link between feeding and produced milk isotopic signals. [22][23][24][25]36 In the case of this work, analyzing the isotopic carbon and nitrogen ratio values calculated from the mixing model (model 1) (that reflects the feed isotopic signal and the proportion given to the buffaloes), a lower value for 15 N with respect to that measured in milk was found. This result was reported also in Cantalapiedra-Hijar et al, 25 where ruminant animal and milk proteins were found enriched with regards to their diet, due to the metabolic pathways of these animals.…”
Section: Discussionmentioning
confidence: 87%
“…10 The relationship between the isotopic carbon ratios of animal diet (composed by C3 and C4 photosynthetic pathway plants) and of milk produced by cows was investigated in Camin et al, 22 who found a correlation between 13 C of casein and the percentage of maize addicted in the diet. Schneider et al 23 investigated the carbon-13 ( 13 C) discrimination between diet and milk, while Cabrita et al 24 and Cantalapiedra-Hijar et al 25 studied nitrogen fractionation processes in ruminants, which determine the nitrogen signal of milk, starting from the nitrogen signal of eaten plants and so, in turn, influenced by agriculture practice, fertilizer used, climate and nearness to the sea. 10 In Bontempo et al, 26 27 on the bases of stable isotopes signal, linked to the cattle diet and local climate conditions.…”
Section: Introductionmentioning
confidence: 99%